2020
DOI: 10.1002/jts.22506
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Sexual Harassment, Stalking, and Sexual Assault During Military Service Among LGBT and Non‐LGBT Service Members

Abstract: Sexual victimization, including sexual harassment and assault, remains a persistent problem in the U.S. military. Service members identifying as lesbian, gay, bisexual, or transgender (LGBT) may face enhanced risk, but existing research is limited. We examined experiences of sexual harassment, stalking, and sexual assault victimization during service in a sample of LGBT and non‐LGBT active duty service members. Service members who identified as LGBT (n = 227 LGB, n = 56 transgender) or non‐LGBT (n = 276) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 30 publications
3
35
0
Order By: Relevance
“…As evidenced by a sister study, half of LGBT service members interviewed in 2016 continued to fear that the military environment, at both the institutional and interpersonal level, was not yet LGBT inclusive, despite repeal of LGBT bans (McNamara et al, 2020). Furthermore, a recent study found that LGBT service members are at heightened risk of sexual harassment, assault, and stalking than their non-LGBT counterparts (Schuyler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As evidenced by a sister study, half of LGBT service members interviewed in 2016 continued to fear that the military environment, at both the institutional and interpersonal level, was not yet LGBT inclusive, despite repeal of LGBT bans (McNamara et al, 2020). Furthermore, a recent study found that LGBT service members are at heightened risk of sexual harassment, assault, and stalking than their non-LGBT counterparts (Schuyler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Further information on study design, recruitment, and procedures can be found in McNamara et al and Schuyler and Klemmer. 21,22,37 The Human Protection Office of the U.S. military and the institutional review boards at the University of Southern California and University of California, Los Angeles, granted ethical approval for this study.…”
Section: Participantsmentioning
confidence: 99%
“…Other publications from the broader research project describe collection of these items in detail. 21,22,40 Analyses Data cleaning and analyses were completed using Stata version 15.1. 41 Analyses included χ 2 tests to estimate percentages and identify differences between groups (sexual orientation, gender, age, race, partnership status, education level, rank, branch of service, years of service, and deployment history) for further exploration in regression analyses and multinomial logistic regressions to calculate relative risk ratios and adjusted R2.While assessing for missingness in the data, the LGBT Climate Inventory was found to have 8% missingness; multiple imputation was used to impute mean scores for observations missing this measure.…”
Section: Socio-demographic and Military Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Additionally, people who are non-gender conforming and members of the LGBTQ+ (lesbian, gay, bisexual, transgender, queer) community are at disproportionate risk of these experiences. 3,4 People who have experienced MST often share that although they prepared to make the ultimate sacrifice for their country and comrades, they never prepared to be harmed by a "brother or sister in arms," whom they were trained to trust with their life. Some survivors report that an insufficient or even detrimental institutional response when reporting MST was as distressing as the initial trauma.…”
Section: Providing Care To Survivors Of Military Sexual Traumamentioning
confidence: 99%